Ecological Purchases Made by Managers in Hotel Industry. An Approach of the Main Determining Factors - Mirela Ştefănică; Ana Iolanda Vodă; Rodica Cristina Butnaru; Gina Ionela Butnaru; Mircea Gabriel Chiriţa (Amfiteatru Economic)
Lately, there has been an intensification of the concern for environmental protection and development of an ecological attitude and behaviour among the operators in tourism industry. Consequently, ecological purchases have become important components in establishing hotel environmental strategies and in the customers’ consumption behaviour. Most of the researchers present this very attitude of the customers regarding the green products and their intention to buy them. The present research approaches ecological purchases from the hotel managers’ perspective, by analysing the relationships among them, and the environmental attitude, environmental problems, and the benefits motivating the managers to make ecological purchases in 92 hotels in Romania. In this research we used the frequency analysis, scale reliability, and multiple linear regression analysis (the method of the least squares). The data were analysed with the help of STATA program, and the results support the research hypotheses, showing that the influence of the environmental attitude and of the economic benefits on ecological purchases is important. The results show a significant and positive relationship among the ecological purchases, the environmental attitude, and the associated benefits. In addition, the study identifies a negative relationship between the ecological purchases and the environmental concern. Furthermore, hotel classification has a negative influence on the ecological purchases made by their managers. The implications, limits, and future lines of research are also mentioned in this study